(untitled) (Eurasian Journal of Ecology, 2016)
Was studied on the influence of culture filtrate (CF) of the root rot on the development, morphogenesis and regeneration of different soybean varieties. It was revealed that 10% of the concentration of CF morphogenesis was more intense. At 30% concentration of CF had a depressing effect. The seeds obtained potentially resistant to root rot from regenerated plants were transferred to soybean breeders.